Pengatur Suhu dan Kelembaban Kumbung Jamur Otomatis - Nugroho, Aji; Asyroh, Muhammad Fakhril Kaffah; Pangestu, Aji; Wulandari, Bekti (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2018)
Temperature and humidity have an important role in the cultivation of oyster mushrooms to obtain optimal growth of oyster mushrooms. The optimum temperature required ranges from 24 ° C - 27 ° C and 80% - 90% humidity. The watering of mushroom kumbung should be done regularly, in order to maintain the temperature and humidity of the surrounding air, then conducted research that aims to create a tool that can regulate the temperature and humidity kumbung mushrooms automatically to facilitate farmers keep the temperature and humidity stability continuously. This automatic adjustment system uses DHT-11 sensors as air and humidity and arduino uno gauges as tool controls. Tests conducted for 7 days with data collection in the morning at 06:00 AM, noon at 12:00 PM and afternoon at 4:00 PM. The test results prove that this system of temperature and humidity regulator can keep the stability of room temperature and humidity with an average 25°C of room temperature and 60% of humidity with set point temperature at 27°C and 55% of humidity.